Synthesis of poly(dimethylsiloxane)-block-poly[3-(triisopropyloxysilyl) propyl methacrylate] and its use in the facile coating of hydrophilically patterned superhydrophobic fabrics1. Issue 49 (30th May 2015) - Rabnawaz, Muhammad; Wang, Zijie; Wang, Yu; Wyman, Ian; Hu, Heng; Liu, Guojun
<x xml:space="preserve">Abstract</x> We report the synthesis and applications of a novel poly(dimethylsiloxane-block-poly[3-(triisopropyloxysilyl)propyl methacrylate]) (PDMS-b-PIPSMA) diblock copolymer.